Migration Problems of Chinese Women - Lee, Christina C.; Cochran, Larry R. (Canadian Journal of Counselling and Psychotherapy, 2011)
Using a case study approach focusing on the adjustment decisions of 15 women who emigrated from Hong Kong to Vancouver, British Columbia, this article clarifies the implications for cross-cultural counselling drawn from the results. In particular, adjustment seems to be characterized by potent conflicts located in everyday practical situations. Common themes of conflict involve Chinese and Western value opposition, the need for personal development, and the fear of social isolation. Six different patterns of client adjustment are indicated that may be useful to counsellors in their work with immigrant women.